Links between technology and philosophy: The specific case of the metaverse ecosystem: Philosophical categorization of technological terms from the Summa Theologica of St. Thomas - Grimaldi D'Esdra, Sophie; Hernández Ruiz, Victoria; Mohedano Martínez, José Miguel; Ramón Reyero, Eva (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The development of technology and artificial intelligence has been raising ethical and anthropological questions for years. The Summa Theologica of St. Thomas allows us to categorize technological terms and establish ontologies in a philosophical key. Using the methodology of the Summa, the term “metaverse” and its ethical implications will be studied here. The article also provides a systematic review of scientific literature to elaborate a map of knowledge from a qualitative and quantitative point of view that makes visible the impact of this emerging terminology in research.